Late Blight of Potato and Tomato - Ryan Donahoo; Pamela Roberts (EDIS)
Both potato and tomato are susceptible to late blight, an aggressive disease capable of rapidly destroying entire fields. The disease is distributed worldwide and occurs wherever tomatoes or potatoes are grown, and conditions favor disease development. This 4-page fact sheet was written by Ryan Donahoo and Pamela Roberts, and published by the UF Department of Plant Pathology, December 2012.